2012
DOI: 10.1111/j.1467-9310.2012.00691.x
|View full text |Cite
|
Sign up to set email alerts
|

The university entrepreneur: a census and survey of attributes and outcomes

Abstract: This study looks at 400 technology transfer disclosures and their inventors over a 10-year period at a large US research university. We find that faculty productivity in terms of patenting is not related to commercialization success, but entrepreneurial qualities are significantly correlated. Results indicate that the significant factors in successfully forming a university spin-out are the level of experience of the faculty member and participation in an industry sponsored research agreement. We also find tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 43 publications
1
21
0
7
Order By: Relevance
“…In line with Marion et al (2012), our results suggest that to reinforce academic entrepreneurship, universities should incorporate entrepreneurial achievements into their promotion and tenure policies, clearly taking into account policies to promote entrepreneurial thinking and learning, as highlighted above. Moreover, with a view to complementing Huyghe and Knockaert's (2015) conception that the changing organisational culture is essential to stimulate researchers to engage in entrepreneurship, we put forward the idea that organisational culture always needs to be complemented by a revised reward system to achieve this aim.…”
Section: Discussionsupporting
confidence: 56%
“…In line with Marion et al (2012), our results suggest that to reinforce academic entrepreneurship, universities should incorporate entrepreneurial achievements into their promotion and tenure policies, clearly taking into account policies to promote entrepreneurial thinking and learning, as highlighted above. Moreover, with a view to complementing Huyghe and Knockaert's (2015) conception that the changing organisational culture is essential to stimulate researchers to engage in entrepreneurship, we put forward the idea that organisational culture always needs to be complemented by a revised reward system to achieve this aim.…”
Section: Discussionsupporting
confidence: 56%
“…For example, Tartani and Breschi (2012) found out that a researcher's decision to collaborate with industry is significantly influenced by the perceived threats to a researcher's academic freedom. However, it seems that the majority of the authors (Siegel et al, 2004;Van Looy et al, 2004;Marion et al, 2012) have seen this as a natural evolution of the university system and the relationships can be mutually beneficial, as was in in the case of teaching and research earlier (Etzkowitz, 2003). Furthermore, in the universities of the technology in Finland with a more pragmatic goal setting, this has not become a great issue.…”
Section: Different Project Types and Interest Groupsmentioning
confidence: 88%
“…7, 17 % of all patents are transferred by individual inventors, which can be explained by previous studies addressing the importance of networks of academic scientists and industry professionals (Aldridge and Audretsch 2011;Colyvas et al 2002;Thursby and Thursby 2002). Additionally, 'entrepreneurial experience' and 'inclination toward commercialisation' are two inventor characteristics that have been shown to be of significant importance in commercialisation of academic research (Marion et al 2012). Our finding is in line with prior work which has found that researchers bypass their TTO (Audretsch et al 2006;Fini et al 2010;Markman et al 2008a, b).…”
Section: The Autonomous Bridge and Corporate Modes Of Patent Transfermentioning
confidence: 89%